Active Switching of Toroidal Resonances by Using a Dirac Semimetal for Terahertz Communication - Sun, Yuanbao; Liao, Denggao; Xu, Jinjin; Wu, Yiping; Chen, Lin (Frontiers in Physics, 2020)
The dynamical switching of a toroidal dipole resonance channel is demonstrated by tuning the Fermi level of a Dirac semimetal film sandwiched between the back substrates. As the Fermi level is increased from 30 to 150 meV, the resonance frequency is switched from 0.283 to 0.201 THz because of the transition from toroidal mode to hybrid mode. The hybrid mode is formed by the interaction between the toroidal mode and the plasmonic mode (induced by a Dirac semimetal film with metallic properties). The influence of the sandwiched dielectric layer (between the toroidal metasurface pattern and the Dirac semimetal film) on the switching effect was also investigated. This active dual-channel terahertz switching may have potential applications in advanced terahertz communication.